Investigating the reproductive potential and yield of pecans [Carya illinoinensis (Wangenh. K. Koch)] under South African conditions. - Snyman, Tertius Jacobus (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScAgric)--Stellenbosch University, 2021.